Does BioGlue contribute to anastomotic pseudoaneurysm after thoracic aortic surgery? - Ma, Wei-Guo; Ziganshin, Bulat A.; Guo, Chang-Fa; Zafar, Mohammad A.; Sieller, Richard S.; Tranquilli, Maryann; Elefteriades, John A. (Journal of Thoracic Disease, 2017)
Background: Although bovine serum albumin-glutaraldehyde glue (BioGlue®) has been successfully used as a hemostatic adjunct in aortic surgical procedures, there are reports that it may lead to anastomotic pseudoaneurysm formation. We seek to examine if the use of BioGlue is associated with a high incidence of anastomotic pseudoaneurysm formation following surgical repair of thoracic aortic disease. Methods: We reviewed the medical records and follow-up computed tomography (CT) scans of patients from 2001 to 2015 in whom BioGlue was used during surgical repair of thoracic aortic disease to detect postoperative anastomotic pseudoaneurysm formation. Results: A total of 233 patients with BioGlue use were identified. Mean age was 63.5±14.0 years (median 66; range 14–88; 25–75%, IQR 54–74 years) and 149 were male (63.9%). Surgical indication was thoracic aortic aneurysm in 169 (72.5%) patients, aortic dissection in 49 (21.0%), intramural hematoma in 9 (3.9%), penetrating aortic ulcer in 3 (1.3%) and other in 3 (1.3%). Emergency/urgent surgery was performed in 68 cases (29.2%). Operative mortality was 7.3% (17/233). Re-exploration for bleeding and neurologic deficits occurred in 24 (10.3%) and 21 (9.0%) patients respectively. All operative survivors were followed (100%, 216/216) and CT follow-up was available in 81.9% (177/216) for a mean duration of 2.4 years (median 0.6; 25–75% IQR 0.2–3.6 years). Anastomotic pseudoaneurysm was detected in 1 patient (0.6%) at 3 years postoperatively. This was an elderly female with extremely frail tissues who underwent a reoperative ascending and arch replacement for dissection. Conclusions: The use of BioGlue in thoracic aortic surgery was not associated with excess incidence of anastomotic pseudoaneurysm formation following surgical repair of thoracic aortic disease. Its use need not be discouraged on this basis.